The day my mother left - Prosek, James 1975- (New York Simon & Schuster Books for Young Readers, 2007)
When his mother leaves to live with another man, nine-year-old Jeremy faces his own pain and loss, his father's depression and sister's distance, the pity of friends and strangers, and his father's remarriage two years later, finding solace in fishing and his artwork.
UCWS-2014-G-1612 donated by Ana P. Santos
Keywords: Families -- Juvenile fiction; Drawing -- Juvenile fiction; Fishing stories; Depression, Mental -- Juvenile fiction; Divorce -- Juvenile fiction; Remarriage -- Juvenile fiction; Family problems -- Fiction; Drawing -- Fiction; Fishing -- Fiction; Depression, Mental -- Fiction; Divorce -- Fiction; Remarriage -- Fiction